Jesus and John Wayne: how white evangelicals corrupted a faith and fractured a nation - Du Mez, Kristin Kobes (Liveright Publishing Corporation, 2021)
"A scholar of American Christianity answers perhaps the most bewildering question of our time: Why are evangelicals "the Donald's" most fervent supporters? Donald Trump is a libertine who lacks even basic knowledge of the Christian faith. Yet in 2016 he won 81 percent of the white evangelical vote, and continues to rely on white evangelicals as his base of support. While we assume the religious right has pragmatic reasons for backing Trump, in truth he represents the fulfillment of evangelicals' most deeply held values. As historian Kristin Kobes Du Mez demonstrates, American evangelicals have worked for decades to replace the Jesus of the Gospels with an idol of rugged masculinity and Christian nationalism-or, in the words of one modern chaplain, with "a spiritual badass." Trump is hardly the first flashy celebrity to capture evangelicals' hearts and minds, having followed the path blazed by, among others, John Wayne, Oliver North, and Mel Gibson. A revelatory account of a uniquely influential subculture, Jesus and John Wayne incisively reveals why evangelicals have rallied behind patriarchal power and the least- Christian president in American history"--